Efektivitas Chin Tuck Against Resistance (CTAR) pada Disfagia Orofaringeal Paska Stroke: Studi Meta-Analisis - Junaeni, Junaeni; Alythea, Najma (Akademi Terapi Wicara, 2023)
This study aims to examine the effectiveness of the chin tuck against resistance (CTAR) approach in reducing aspiration and increasing oral intake in individuals with post-stroke swallowing disorders. This study was a systematic review and meta-analytical design. Electronic database in the form of PubMed is used to search related data. Three experimental articles with a randomized controlled trial (RCT) design were included in this study. Based on related results, it is known that CTAR has an effect on reducing aspiration rate (SMD = -1.03; 95% CI -1.72 – -0.35) and it is known that CTAR has an effect on increasing oral intake (SMD = 0.82; 95% CI 0.03 – 1.61) .